Pest categorisation of Ips cembrae - Jeger, Michael (John Wiley and Sons Inc., 2017)

(untitled) (EFSA J)
The Panel on Plant Health performed a pest categorisation of the large larch bark beetle, Ips cembrae (Heer) (Coleoptera: Curculionidae, Scolytinae), for the EU. I. cembrae is a well‐defined and distinguishable species, native to Europe and recognised mainly as a pest of larch (Larix spp.) and occasionally of pine (Pinus spp.) and spruce (Picea spp.). It is distributed in 16 Member States of the EU and listed in Annex IIB of Council Directive 2000/29/EC. Protected zones are in place in Greece, Ireland and the United Kingdom (Northern Ireland and Isle of Man). Wood, wood products, bark and wood packaging material are considered as pathways for this pest, which is also able to disperse by flight. The insects normally establish on fallen or weakened trees but, when their populations are high, can also mass‐attack healthy trees. The males produce aggregation pheromones that attract conspecifics of both sexes. The insects also inoculate pathogenic fungi to their hosts. There are one to two generations per year. Before establishing their broods, the young adults need to proceed to maturation feeding either within the bark of the tree where they developed or in 2–18 years old twigs. I. cembrae has been expanding its geographical range in Europe during the second half of the 20th century. Sanitary thinning or clear felling is the major control methods. Quarantine measures are implemented to prevent entry in the protected zones. All criteria for consideration as potential protected zone quarantine pest are met. The criteria for considering I. cembrae as a potential regulated non‐quarantine pest are not met since plants for planting are not viewed as a major pathway.